Visitor Opinion on Wildlife Activities at Kuala Gandah National Elephant Conservation Centre, Pahang, Malaysia - Daud, Darishawati (2009)
Human-wildlife interactive experience has become a popular recreational pursuit in the wildlife-based tourism. Many tourists seek close interaction with wild animal in a safe while in its natural or semi-natural settings. The interface between people who desired to be with animal in its habitat is able to create closeness atmosphere. Such experience could result in better appreciation of wild animals and sustainability of the wildlife interactive base tourism. This study was conducted in Kuala Gandah National Elephant Conservation Centre (KGNECC). The Department of Wildlife and National Park (DWNP) set aside a portion of the Krau Forest Reserve Pahang for the centre. The centre also takes care of the orphaned and abandoned elephants. The main objective of this study was to determine the factors in visiting KGNECC that related with the human-wildlife interactive activity.These factors are to be considered as the basis for sustainability of KGNECC visitors-wildlife interactive activity. In this study, questionnaires were distributed using convenience sampling technique to 400 visitors in order to get responses related to the wildlife interactive activity. The questionnaire were administered using structured questions that covers on respondents’ opinions on KGNECC regarding the visitation attributes, preferences in tourism activities particularly on the wildlife tourism activities, including their level of interaction with the wildlife and their relationship between the types of wildlife tourism activities and the level of interactions that have occurred.